Clinicopathological characteristics of liposarcoma- ten years experience in a single institution - Alduais, Saleh Abdulkadir Saeed (2023)
Liposarcomas are a rare adipocytic soft tissue sarcoma. It is primarily classified into five subtypes according to the recent 2020 WHO classification. However, its heterogeneous morphology consistently presents a diagnostic problem to most pathologists, leading to inappropriate patient management. The study focuses on our institution's clinicopathologic aspects of liposarcoma and its clinical outcome. We retrospectively collected 79 cases of archived lipomatous tumours (larger than 10 cm in size), diagnosed from January 2010 to December 2020, from the Pathology Department at HUSM. The histopathology slides were reviewed. The clinicopathological data were retrieved from the medical records and histopathology reports. Results: Fifty-two of the 79 cases were histologically evaluated as lipomas. The remaining 27 cases were liposarcomas. The median age of patients with lipoma and liposarcoma was similar (52 years). Atypical lipomatous tumour/well-differentiated liposarcoma (ALT/WDLS) and myxoid liposarcoma were the two most prevalent subtypes, accounting for 40.7% of cases. The overall recurrence rate for liposarcoma was 37%, with histological grade being the most significant predictor for recurrence [β = 5.93, p < 0.001]. However, distant metastasis did not show a significant association with histological subtypes (p = 0.115). There is no significant difference in the clinical outcomes of large lipomas and ALT/WDLS after surgical excision. Due to their morphologic heterogeneity, lipomatous tumours can be challenging to diagnose. Molecular testing of the MDM2 and CDK4 genes is increasingly important to reduce morbidity and mortality. Future research should examine whether amplified MDM2 and CDK4 have synergistic or opposite effects on prognosis and targeted treatment.